Modern Tendencies in the Play “Sick Dojchin” by Georgi Stalev - Trajce Stameski (VERMILION International Journal of Literature and Art, 2017)
In the short review of Georgi Stalev’s works, in “The History of Macedonian Literature of the 20th Century”, Miodrag Drugovac considers that “the lyrical play “Sick Dojchin” (1971) is a text that portrays the Macedonian past through legendary suggestions. Transforming the motive about Sick Dojchin, contrary to the heroic ground of the epic poem, Stalev’ s play transforms into introspective discourse about the suffering of the human soul. This puts Georgi Stalev among the first authors from the contemporary Macedonian drama literature who have created modern tragedy. Especially in this context we can discuss thetheoretically-terminologically and literary-aesthetical specification of these plays as modern-ones.
Keywords: Modernism, tragedy, folk tradition, Sick Dojchin, contemplative play